2005
DOI: 10.1063/1.2000667
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional simulation on current-density distribution in flip-chip solder joints under electric current stressing

Abstract: Three-dimensional simulations on current-density distribution in solder joints under electric current stressing were carried out by finite element method. Five underbump metallization (UBM) structures were simulated, including Ti∕Cr–Cu∕Cu thin-film UBM, Al∕Ni(V)∕Cu thin-film UBM, Cu thick-film UBM, Ni thick-film UBM, and Cu∕Ni thick-film UBM. The maximum current density inside the solder occurs in the vicinity of the entrance of the Al trace into the solder joint, while there is no obvious current crowding eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 8 publications
1
31
0
Order By: Relevance
“…This are was believed to have the highest local current density and the highest degree of current crowding initially. [2][3][4][5][6][7][8][9][10] Figure 5 is a zoom-in image for the left side of the void shown in Fig. 2b.…”
Section: Osp Surface Finishmentioning
confidence: 97%
See 1 more Smart Citation
“…This are was believed to have the highest local current density and the highest degree of current crowding initially. [2][3][4][5][6][7][8][9][10] Figure 5 is a zoom-in image for the left side of the void shown in Fig. 2b.…”
Section: Osp Surface Finishmentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] To counter the negative effects caused by high current density, several approaches have been proposed and deployed. Two well-known approaches involve better circuit and interconnect designs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the marker movement at the low-current-density region (nos. [1][2][3][4][5] was in the opposite direction, against the electron flow. This interesting phenomenon will be discussed later.…”
Section: Resultsmentioning
confidence: 99%
“…By using the finite-element method to simulate current distribution, it was found that the current density in the currentcrowding area can be one order of magnitude higher than the average density in the solder bump. 3,4 The effect of current crowding on pancake-type void formation at the cathode and whisker growth at the anode of solder joints has been reported. [5][6][7] However, the effect of nonuniform distribution of electric current on diffusion in the bulk of the solder bump is unclear, and no direct measurement of the rate of electromigration in the current-crowding region versus that in the rest of the solder bump has been reported.…”
Section: Introductionmentioning
confidence: 98%
“…For the solder joint with Al/ Ni(V)/Cu thin-film UBM, the maximum current density is 1.11 · 10 5 A/cm 2 and the maximum temperature is 98.8°C in the solder, as reported in our previous publications. 14,20 For the solder joint with the 5-lm Cu UBM, the maximum current density was 4.37 · 10 4 A/cm 2 and the hot-spot temperature was 89.5°C in the solder. The MTTF would be 3.3 times longer than that with the Al/Ni(V)/Cu UBM under 0.567 A at 70°C.…”
Section: Discussionmentioning
confidence: 99%